TIL VA TAFAKKUR («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the relationship between language and culture, language and thought the linguistic and cultural significance of the language is discussed.
Keywords: Language and culture, language and thinking, linguocultural units, W. Humboldt.